2015
DOI: 10.1007/s11096-015-0143-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of CYP2C19 genotype with plasma voriconazole levels: a preliminary retrospective study in Indians

Abstract: Plasma voriconazole levels are influenced by CYP2C19 variants, drug interactions and clinical condition of the patient. Genotype assessment at initiation of therapy followed by drug monitoring would help optimizing therapeutic efficacy and minimizing toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Similarly, many studies also showed CYP2C19 polymorphisms have an extensive effect on VRC C min . Comparable with previous findings , C min was increased in the PMs as compared with that in both the IMs and the EMs in the present study. Moreover, the distribution of CYP2C19 varies in different ethnic populations.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, many studies also showed CYP2C19 polymorphisms have an extensive effect on VRC C min . Comparable with previous findings , C min was increased in the PMs as compared with that in both the IMs and the EMs in the present study. Moreover, the distribution of CYP2C19 varies in different ethnic populations.…”
Section: Discussionsupporting
confidence: 83%
“…polymorphisms are believed to be a crucial determinant of the extensive pharmacokinetic variability of VRC . It has been suggested that the optimization of VRC therapy should be based on CYP2C19 genotype . Other sources of variability include age, liver function, comedications and inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…It is probably because the gain-of-function allele CYP2C19*17 is unable to completely compensate for the loss-of-function allele CYP2C19*2. 15 Further, the distribution in different populations is distinctly different from various studies, 30 33 which showed that Caucasians have a high frequency of *17 allele (49%) 34 , while other ethnic groups, especially Chinese, have a high frequency of *2 allele (Table 6 ). The proportion (∼50%) of slow metabolizers in Chinese is far above the average level of other Asian populations (15%–20%), 27 , 29 indicating that Chinese are susceptible to altered pharmacokinetic of VRC due to slow metabolism.…”
Section: Discussionmentioning
confidence: 81%
“…The statistically significant result notwithstanding, the predictive value for those four patients homozygous to the CYP2C19*2 variant allele is not convincingly demonstrated. I believe that the inference made to better patient care is perhaps too speculative and holds little scientific justification from the study results [1].…”
mentioning
confidence: 95%
“…In this issue of IJCP, Chawla et al [1] report on an association between CYP2C19 genotype and plasma voriconazole levels. Based on retrospective data on voriconazole dose, plasma concentration levels, and CYP2C19 genotypes in 55 patients, the authors conclude, ''…voriconazole monitoring and genotype analysis may assist in clinical practice and better patient care'', and suggest impact on clinical practice: ''CYP2C19 genotype and voriconazole monitoring at initiation……is required to achieve therapeutic targets''.…”
mentioning
confidence: 99%